PERLUNY A EVALUASI KINERJA PARASITOID PADA HAMA DAUN KELAPA : BRONTISPA LONGISSIMA GESTRO (COLEOPTERA: CHRYSOMELIDAE) DI KABUPATEN ENDE-FLORES - Wahyuni, Sri (AGRICA, 2008)
Brontispa longissima Gestro (Coleoptera: Chrysomelidae) is ones of the most important pest who attack of many family palms in South East Asia. In Indonesia, Brontispa longissima has. becomes a primer pest on coconut. It was Decreasing yield result up to 30 - 40 % returns and 5% of the attacked crops will die. Ones of the failed reason of control action is a low preventive system on every territory entrance, otherwise, coconut was a needful and fast-moving commodity for people and industry. The second reason is secondary commodity assumes and low cropping system caused pest and disease uncontrolled. Three bio-control usages on-field need to monitored caused farmers incapable. The success indicator for parasitoid release was quick and easy to adapt for the parasitoid. It was related " three-generation three years," theory by Ev Clausen, the expert of integrated pest and management control from California says: a) The perfectly of Effective parasitoid/predator always quick and easy to adapt, b) The failed parasitoid/predator to adapt easily and quickly was an ineffective indicator for bio-control, c) Parasitoid release or exotic predator could be stopped for 3 years if no evidence adapt on fields. According to the experts, the key for the success of system controlling above depends on cropping agroecosystem stability.